Genetic approaches to the investigation of serotonergic neuron functions in animals - U. S. Drozd; E. V. Shaburova; N. N. Dygalo (Вавиловский журнал генетики и селекции)
The serotonergic system is one of the most important neurotransmitter systems that take part in the regulation of vital CNS functions. The understanding of its mechanisms will help scientists create new therapeutic approaches to the treatment of mental and neurodegenerative diseases and find out how this neurotransmitter system interacts with other parts of the brain and regulates their activity. Since the serotonergic system anatomy and functionality are heterogeneous and complex, the best tools for studying them are based on manipulation of individual types of neurons without affecting neurons of other neurotransmitter systems. The selective cell control is possible due to the genetic determinism of their functions. Proteins that determine the uniqueness of the cell type are expressed under the regulation of cell-specific promoters. By using promoters that are specific for genes of the serotonin system, one can control the expression of a gene of interest in serotonergic neurons. Here we review approaches based on such promoters. The genetic models to be discussed in the article have already shed the light on the role of the serotonergic system in modulating behavior and processing sensory information. In particular, genetic knockouts of serotonin genes sert, pet1, and tph2 promoted the determination of their contribution to the development and functioning of the brain. In addition, the review describes inducible models that allow gene expression to be controlled at various developmental stages. Finally, the application of these genetic approaches in optogenetics and chemogenetics provided a new resource for studying the functions, discharge activity, and signal transduction of serotonergic neurons. Nevertheless, the advantages and limitations of the discussed genetic approaches should be taken into consideration in the course of creating models of pathological conditions and developing pharmacological treatments for their correction.